FORMULASI DAN UJI AKTIVITAS ANTI BAKTERI GEL PEMBERSIH TANGAN EKSTRAK ETANOL MIDING (STENOCHLAENA PALUSTRIS) - Ratih Indrawati (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2020)
Background Kalimantan is the largest island in Indonesia which has a tropical climate with abundant biological resources. Biodiversity has the potential to be used as medicinal plants. Plant extracts are preferred as antibacterial, one of which is miding plant (Stenochlaena palustris).Aim This study aims to find out the potential of miding plant extracts as an antibacterial against Staphylococcus aureus.Method Miding was extracted using maceration using 70% ethanol solvent. Ethanol miding extraction showed a yield of 3.12% (w / w).Result The extract obtained was carried out by phytochemical test, phytochemical test of miding ethanol extract showed the composition of alkaloid, flavonoid, stereoid, phenolic, and saponin groups.Conclusion Antibacterial activity test results using the well diffusion method. Formula 30%, 20 and 10%. Obtained inhibition zone diameter of 12.50 mm and 20% of 12.00 mm showed greater antibacterial activity compared to a comparison of only 10.02%.